Online Family Problem-Solving Therapy (F-PST) for Executive and Behavioral Dysfunction After Traumatic Brain Injury in Adolescents: A Randomized, Multicenter, Comparative Effectiveness Clinical Trial. Issue 3 (May 2020) - Kurowski, Brad G.; Taylor, H. Gerry; McNally, Kelly A.; Kirkwood, Michael W.; Cassedy, Amy; Horn, Paul S.; Stancin, Terry; Wade, Shari L.
Abstract : Objective: To examine the comparative effectiveness of 3 modes of family problem-solving therapy (F-PST): therapist-guided online, self-guided online, and face-to-face. Setting: Four children's hospitals and a general hospital with pediatric commitment. Participants: A total of 150 adolescents aged 14 to 18 years, previously hospitalized with traumatic brain injury (TBI), and evidence of behavior problems at enrollment. Design: Multicenter, randomized clinical trial. Main Measures: Behavior Rating Inventory of Executive Function (BRIEF) Global Executive Composite (GEC), Behavior Regulation Index, and Metacognition Index, and Strengths and Difficulties Questionnaire (SDQ) Total at baseline and 6 and 9 months later. Results: Mixed-model intention-to-treat analyses of comparative effectiveness failed to reveal statistically significant differences among treatment groups. At 6 months, parent BRIEF-GEC improved for the therapist-guided and self-guided, online groups. Effects remained significant and increased in magnitude at 9 months for the self-guided online group. Scores for the Self-guided online group significantly improved from baseline to 9 months on the SDQ Total. Conclusions: This comparative effectiveness study supports the utility of both self- and therapist-guided online F-PST in improving executive function behaviors in adolescents following TBI. Further work regarding clinical implementation and how best to integrate telehealth with ongoing rehabilitation care is warranted.